2020
DOI: 10.1002/ange.202002593
|View full text |Cite
|
Sign up to set email alerts
|

Engraving the Surface of Electrospun Microfibers with Nanoscale Grooves Promotes the Outgrowth of Neurites and the Migration of Schwann Cells

Abstract: We report a simple method based upon coaxial electrospinning for the fabrication of aligned microfibers engraved with nanoscale grooves to promote neurite outgrowth and cell migration. The success of this method relies on the immiscibility between poly(ϵ‐caprolactone) (PCL) and poly(vinyl pyrrolidone) (PVP) in 2,2,2‐trifluoroethanol (TFE) for the generation of PVP/TFE pockets on the surface of a PCL jet. The pockets are stretched and elongated along with the jet, eventually resulting in the formation of nanosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…However, the incorporation of these features is shown to increase the roughness of electrospun fibers and, in turn, increase cell adhesion and proliferation [ 130 , 131 ]; thus, we can hypothesize that these features may promote increased adhesion and proliferation of Schwann cells as well. Nano-grooved electrospun fibers, formed through phase separation and the subsequent stretching of the fibers during the electrospinning process, are shown to have beneficial effects on Schwann cells in vitro [ 132 , 133 ]. Huang et al found that the presence of nanogrooves on electrospun cellulose acetate butyrate fibers improved Schwann cell elongation compared to smooth fibers [ 132 ].…”
Section: Peripheral Nervous System Glia and Electrospun Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the incorporation of these features is shown to increase the roughness of electrospun fibers and, in turn, increase cell adhesion and proliferation [ 130 , 131 ]; thus, we can hypothesize that these features may promote increased adhesion and proliferation of Schwann cells as well. Nano-grooved electrospun fibers, formed through phase separation and the subsequent stretching of the fibers during the electrospinning process, are shown to have beneficial effects on Schwann cells in vitro [ 132 , 133 ]. Huang et al found that the presence of nanogrooves on electrospun cellulose acetate butyrate fibers improved Schwann cell elongation compared to smooth fibers [ 132 ].…”
Section: Peripheral Nervous System Glia and Electrospun Fibersmentioning
confidence: 99%
“…Huang et al found that the presence of nanogrooves on electrospun cellulose acetate butyrate fibers improved Schwann cell elongation compared to smooth fibers [ 132 ]. Further, Wu et al observed greater maximum and average Schwann cell migration on nano-grooved electrospun PCL fibers compared to smooth PCL fibers [ 133 ].…”
Section: Peripheral Nervous System Glia and Electrospun Fibersmentioning
confidence: 99%
“…Grooved structures are considered very effective in promoting axonal guidance, as they can provide more sensing targets and appropriate contact areas for the growth cones of neuritis [46]. Micropatterned pure-SF hydrogels (Topo@TPSF) were successfully fabricated by in situ micromolding with PDMS stamps.…”
Section: Mechanical Property and Surface Topologymentioning
confidence: 99%
“…In addition, the secondary morphology of fibers has an important effect on the properties of fibers. In the past few decades, the preparation of porous fibers [20], wrinkled fibers [21] and grooved fibers [22] by electrospinning has been reported. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the composition and structure of electrospun fiber can improve and change their properties and applications. The common secondary structure of the electrospinning fiber is porous [23][24][25][26], hollow [27][28][29][30], groove [22,31,32], belt-like [33], etc. The coarse surface of grooved fibers is conducive to cell adhesion, and the orientation of groove fibers can induce axon growth well, so groove fibers can be used for tissue engineering [34].…”
Section: Introductionmentioning
confidence: 99%